2021
DOI: 10.1002/pc.26036
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and performance evaluation of waste cotton and polyester fiber‐reinforced green composites for building and construction applications

Abstract: This research reports thermoset composites reinforced with cotton and polyester fibers (recovered from pre‐consumer textile waste). The carded web of cotton and polyester fibers and epoxy resin were used to develop the composites using the compression molding technique. The polyester/epoxy composites show average tensile and impact strength higher than cotton/epoxy composites. However, cotton/epoxy composites show average flexural strength higher than polyester/epoxy composites. The bearing strength in a pinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Bamboo fiber polyesterreinforced composite 126.2 Tarabi et al [36] Waste cotton and polyester fiberreinforced green composites 93.64 Kamble and Behera [37] Hibiscus tiliaceus fiberreinforced bisphenol composite 400 Purnowidodo et al [38] increase in tensile strength with 10% ASP/AP filler was due to the formation of homogeneous ESP and AP filler distribution in polyester-TF matrix. [40] The increase in tensile strength with 10% ESP/AP filler indicated that filler powder was able to fill the micro pores of TF and polyester matrix.…”
Section: This Investigationmentioning
confidence: 99%
“…Bamboo fiber polyesterreinforced composite 126.2 Tarabi et al [36] Waste cotton and polyester fiberreinforced green composites 93.64 Kamble and Behera [37] Hibiscus tiliaceus fiberreinforced bisphenol composite 400 Purnowidodo et al [38] increase in tensile strength with 10% ASP/AP filler was due to the formation of homogeneous ESP and AP filler distribution in polyester-TF matrix. [40] The increase in tensile strength with 10% ESP/AP filler indicated that filler powder was able to fill the micro pores of TF and polyester matrix.…”
Section: This Investigationmentioning
confidence: 99%
“…27 In the previous study, first untreated cotton waste (CtW), along with aluminum hydroxide (AH) and boric acid (BA) under different filler loadings first were used in EPN resin for the examination of the mechanical, thermal, and flammability properties of composites. 13 In studies that were different from our study in terms of both filler-type and resin, cotton fabric wastes were used in thermoset unsaturated polyester resin, 28,29 also in epoxy, polyester orthophthalic, and polyurethane resins. 30 In another study, cotton waste which was obtained from a cotton processing mill was utilized to produce the composite panels, but in combination with red pine wood and 10 wt% ureaformaldehyde resin.…”
Section: Introductionmentioning
confidence: 87%
“…The average consumption of textiles per person has increased from 7 kg in 1992 to 13 kg in 2013. According to one forecast, about 148 million tons of waste textiles will be produced in 2030, and more than 150 million tons of waste clothing will be incinerated or landfilled in 2050 [ 5 ]. The main components of textile wastes are polyester and cotton, which mainly include three categories, namely clothing, household materials and industrial textiles, which are mainly prepared by polyester and cotton [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%